Balanced Scorecard as an instrument for responsible management - Stříteská, Michaela (Univerzita Pardubice, 2009)
Balanced Scorecard is reputable and widespread strategic management system that is, however, often criticised from the perspective of corporate social responsibility. Therefore the paper takes closer look at the different possibilities of integrating environmental and social aspects to corporate strategy. The main aim is to demonstrate how Balanced Scorecard could be adapted to become a more responsible framework.
Keywords: Balanced ScoreCard; corporate social responsibility; performance management; strategies